2012
DOI: 10.2174/1876396001205010090
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Mediterranean Soup for Enteral Nutrition and for Prevention of Cardiovascular Diseases

Abstract: Abstract:Background: The Paleolithic diet with fruits, vegetables, roots, leaves, seeds, honey, meat, fish and eggs provided low w-6/w-3 ratio of fatty acids, high monounsaturated fatty acids, fiber, phytochemical antioxidants and proteins. Recent studies indicate that diets similar to Paleolithic diet have anti-inflammatory potential, whereas Western diet, with refined carbohydrates, high w-6/w-3 ratio of fatty acids, lower protein, high in saturated trans and w-6 fat, has proinflammatory effects.Foods that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…Excessive reactive oxygen species cause oxidative damage in the body and are often the result of various human diseases including atherosclerosis, cancer, and aging [1]. Many studies have indicated that intake of foods such as vegetables and fruits containing plenty of antioxidants can reduce the risk of various diseases such as cardiovascular disease and cancer [2]. Therefore, the clinical importance of antioxidant-rich foods has received considerable attention [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Excessive reactive oxygen species cause oxidative damage in the body and are often the result of various human diseases including atherosclerosis, cancer, and aging [1]. Many studies have indicated that intake of foods such as vegetables and fruits containing plenty of antioxidants can reduce the risk of various diseases such as cardiovascular disease and cancer [2]. Therefore, the clinical importance of antioxidant-rich foods has received considerable attention [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The content of ω-3 and ω-6 fatty acids of few edible oils are compared with that of BFSM in Table 7, which shows superiority of the latter with respect to ω-3 fatty acid. It may be worth mentioning that for maintenance of sound health, the ratio of ω-6 to ω-3 fatty acids should be around 1 whereas, the food habit of current lifestyle leads the ratio to be 10:1 to 20:1 (Simopoulos 1991;Singh et al 2012). Thus, to maintain the required ratio, BFSM may be a good source of ω-3 fatty acid contributing to the functionality requirements of consumers.…”
Section: ω-3 Fatty Acid Contentmentioning
confidence: 99%